2022
DOI: 10.3390/ijerph19116697
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Combined Associations between Physical Activity and Sedentary Time with Sleep Quality among Chinese College Students

Abstract: Objective: To investigate the independent and combined associations between physical activity and sedentary time with sleep quality among Chinese college students. Methods: A cross-sectional study was conducted among Chinese college students (N = 2347; M age = 20 years; 67.1% students were female). We used the International Physical Activity Questionnaire—Short Form, the Adolescent Sedentary Activity Questionnaire, and the Pittsburgh Sleep Quality Index to assess the subjects’ physical activity level, sedentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…1 It is recommended that young people aged between 18-25 should fall asleep before 22:00 and have a sleep duration of 7-9 hours per day. 6,15 However, our findings show that only 15.56% of the university and college students go to bed before 22:00, most of them )59.45%( going to bed between 22:00-24:00, and almost 25% going to bed after 24:00, indicating that they tend to stay up late on their own initiative. As has been mentioned above, more than half of them suffering from a long sleep latency, and there are nearly 20% of them cannot obtain a sufficient sleep time, which may have negative effects on their academic performance, physical and mental health, or even suicide behaviors.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…1 It is recommended that young people aged between 18-25 should fall asleep before 22:00 and have a sleep duration of 7-9 hours per day. 6,15 However, our findings show that only 15.56% of the university and college students go to bed before 22:00, most of them )59.45%( going to bed between 22:00-24:00, and almost 25% going to bed after 24:00, indicating that they tend to stay up late on their own initiative. As has been mentioned above, more than half of them suffering from a long sleep latency, and there are nearly 20% of them cannot obtain a sufficient sleep time, which may have negative effects on their academic performance, physical and mental health, or even suicide behaviors.…”
mentioning
confidence: 58%
“…Lacking access to medical help is the most prominent reason, followed by economic pressure, concerns on curative effect, academic pressure, and negligence for sleep disturbance, which may be the major reasons why university and college students' sleep problems increased dramatically from approximately 27% in 1982 to approximately 68% in the last decades. 36 In our study, we found that 92.60% of respondents' monthly living expenses are in 2000 Yuan, which may not be enough for affording the treatment cost of sleep disturbance. As is mentioned above, university and college students have a great pressure on academic study, and sleep disturbance always require periodic treatment, which may have negative influences on their study, thus, resulting in their fear of accepting a treatment.…”
mentioning
confidence: 67%
“…This study examines the factors that affect FMS scores in students who participate in adaptive physical education courses. The results of the research show that the rate of low PA levels among students is 27.7%, which is higher than the 10.0% rate observed among healthy Chinese university students [ 25 ] and the 22% rate observed in other international student populations [ 24 ]. The declining physical fitness of Chinese students has become a matter of widespread concern.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly enough, in this study, people with increased physical activity were more likely to find that their roommates had physical exercise behaviors, suggesting that physical activity behaviors of people around can increase the enthusiasm to exercise and play an important role in the development of a healthy and active lifestyle. However, the results also showed that there was no significant influence of sedentary time on body weight, which probably because students spent a lot of time in classroom and electronic products, and there were already adverse phenomena of insufficient activity and long sedentary time among school students before the epidemic ( Li and Li, 2022 , Carballo-Fazanes et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%